ECONOMIC MOTIVATIONS OF RETURN MIGRATION TO ORIGIN COMMUNITIES IN THE WA WEST DISTRICT, GHANA - Imoro, R. J. (UDS International Journal of Development, 2019)
This paper investigated the economic motivations for the return migration of agricultural labour migrants from southern Ghana to the Wa West District in the Upper West Region. Using a mixed methods research approach which combined structured interviews, in-depth interviews and focus group discussions, a total of 300 returnees were interviewed through a multi-stage, purposive, snowball and convenient sampling techniques. The study established that the return of migrants to their rural origin communities was motivated by the quest to establish business ventures from savings accrued in destination areas, the desire to engage in farming. The acquisition of skills such as mechanics, photographers, seamstresses and tailors which were considered useful for economic survival in origin communities also motivated return migrations. This research has re-enforced the dominance of the economic factors in the return migration discourse. It has also re-echoed the benefits of return migration to origin communities while contributing to the debate on the role of return migration to the development of places of origin. Keywords: Returnees, Economic, Motivations, Origin, Upper West Region